Boycott Campaign Intensity on Consumer Boycott Intentions and Participation: The Role of Access to Substitute Products - Isalman; Ilyas; Farhan Ramadhani Istianandar; Nurul Ittaqullah (Journal of Economics, Business, and Accountancy Ventura, 2025)
This study examines the relationship between the intensity of boycott campaigns and the intention to participate in such campaigns, with a focus on the mediating role of boycott intention and the moderating effect of access to substitute products. Using a correlational approach, data from 210 respondents in the Kendari community who participated in the boycott of pro-Israel products were analyzed through Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings reveal that the intensity of a boycott campaign significantly enhances boycott intention by increasing consumer awareness and involvement. However, campaign intensity does not directly translate into actual participation due to barriers such as skepticism about the boycott’s effectiveness and campaign fatigue. Boycott intention, on the other hand, has a strong positive influence on participation, particularly among consumers motivated by moral and social values. While access to substitute products does not significantly moderate the relationship between boycott intention and participation, its availability positively impacts participation by reducing the personal costs associated with the boycott. Boycott intention serves as the primary mediator between campaign intensity and participation, indicating that more intense campaigns foster greater intention to participate. The study highlights the theoretical and practical importance of understanding campaign intensity, consumer responses, and the role of ethical values and social solidarity in boycott dynamics. Additionally, the availability of substitute products remains a relevant factor in facilitating participation. This research also opens avenues for further exploration into the influence of cultural factors on boycott behavior.